PENGARUH DIGITAL MARKETING, QUALITY PRODUCT DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN ROTI DI HOLLAND BAKERY BATUBULAN - I Ketut Adi Wiranata; Anak Agung Putu Agung; I Made Surya Prayoga (EMAS, 2021)
The purchase decision is a condition in which consumers determine whether they want to buy the product being offered. On the other hand, the expert stated that the purchase decision, namely the Purchase Decision, is a problem-solving process and can be resolved through the process of identifying problems, seeking information, evaluating alternatives, purchasing decisions and post-purchase evaluation. The population in this study were all Holland bakery consumers in the Batubulan area. The sample is part of the number and characteristics of the population. Thus, the sample used is part of the population using random sampling techniques. So the number of samples used is 112 people. Determining the sample by using the formula: N = (5 - 10 x number of indicators for each variable). The results of this study indicate that Digital Marketing, Product Quality, and Brand Image have a positive and significant effect on Bread Purchasing Decisions at Holland Bakery Batubulan, this shows that if Digital Marketing, Product Quality and Brand Image increase, the decision to buy bread at Holland Bakery Batubulan also increases